FRI0351 The Feedback Loop between Long Noncoding RNA NRON and NFAT5 Regulates the Inflammatory Response of Rheumatoid Arthritis Synovial Fibroblasts. (10th June 2014) - Umekita, K.; Trenkmann, M.; Kolling, C.; Michel, B.; Gay, R.; Gay, S.; Frank Bertoncelj, M.
Abstract : Background: Long noncoding RNA (lncRNA) are novel RNA transcripts, emerging as master regulators of gene expression. The lncRNA NRON, noncoding repressor of nuclear factor of activated T cells (NFAT) can repress the cytoplasmic-nuclear translocation and function of NFAT1-4 transcriptional factors. Recently, we have reported that NRON affects also the function of NFAT5, which is known to influence the migration and proliferation of rheumatoid arthritis synovial fibroblasts (RASF). Objectives: To investigate the regulation of NRON expression in RASF and to further analyze its role in regulating the activity of NFAT5. Methods: The expression of NFAT5 protein in RA (n=9) and osteoarthritis (OA) (n=9) synovial fibroblasts was analyzed by immune blotting using α-tubulin for normalization. RASF were transfected with NRON plasmid or with small interfering RNA (siRNA) targeting NRON (n=4) or NFAT5 (n=4) using Lipofectamine 2000. Gene expression in RASF was measured by real-time PCR with normalization to GAPDH or β2-microglobulin. The secretion of IL-6 was analyzed by ELISA. Immunofluorescence microscopy and Western blot of cytoplasmic and nuclear fractions were used to investigate the cytoplasmic nuclear trafficking of NFAT5 in RASF after transfection and/or TNFα (10ng/ml) stimulation. Results: The levels of NFAT5 protein (optical density ± SD: 0.76±0.1 vs 0.54±0.2, p=0.03, n=9 each), NFAT5 mRNA (mean dCt ± SD: 5.1±0.5 vs 5.8±0.7, p=0.01, n=11 each) and NRON (mean dCt ± SD: 11.7±0.7 vs 13.0±0.5, p=0.01, n=11 each) were significantly up regulated in RASF vs OASF. The expression of NRON significantly correlated with the levels of NFAT5 mRNA in RASF (R=0.71, p=0.003). Furthermore, silencing of NFAT5 in RASF led to down regulation of NRON (x-fold ± SD: 0.6±0.3, p=0.05, n=4), indicating that NFAT5 regulates the expression of NRON in RASF. Additionally, TNFα (2h) significantly decreased the expression of NRON in RASF (by 27±25%, p=0.02, n=7);, SB20912 (10μM) the inhibitor of p38MAPK, however, prevented TNFα induced down regulation of NRON in RASF (p=0.01, n=3). Down regulation of NRON in RASF after silencing or TNFα stimulation was accompanied by the translocation of NFAT5 protein from the cytoplasm to the nucleus. NFAT5 target genes, including IL6 (x-fold ± SD: 3.0±2.2, p=0.03, n=4), MMP13 (x-fold ± SD: 4.7±2.0, p=0.03, n=4) and JMJD3 (x-fold ± SD: 1.8±0.2, p=0.003, n=4) mRNAs and IL-6 protein (mean ± SD: 1676±479 vs 2433±504 pg/mL, p=0.007, n=5) were significantly up regulated in RASF after silencing of NRON. Furthermore, overexpressing the lncRNA NRON in RASF suppressed the TNFα induced expression of MMP13 (x-fold ± SD: 0.62±0.2, p=0.02, n=4) and JMJD3 (x-fold ± SD: 0.83±0.1, p=0.02, n=4) mRNAs significantly. Conclusions: We have shown that TNFα down regulates the expression of lncRNA NRON in RASF by enhancing the activity of p38MAPK. Down regulation of NRON in turn results in the increased transcriptional activity of NFAT5 thereby promoting proinflammatory and matrix-destructive responses of RASF. These novel data indicate that a NRON-NFAT5 feedback loop exists in RASF, contributing to their pathogenic characteristics in RA. Acknowledgements: IAR, EURO-TEAM, IMI BTCure. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3213